Dual intuitionistic paraconsistency without ontological commitments - Roetti, Jorge Alfredo (1999)
The issue of this paper is to offer two (dialogical) ways of defending a non committal interpretation of paraconsistency: we will call one the permis sive interpretation and the other the non-ontological commitment interpretation. Stating contradictions and negations is from a permissive point of view of paraconsistency a purely formal matter: lf you do so, so can l. The non-ontological commitment approach results from two rules. One restricts the use and introduction of singular terms to its formal use. The other establishes how to combine the permissive interpretation with this restriction in a second order free logic.